1997
DOI: 10.1088/0268-1242/12/10/013
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and infrared transmission spectroscopies of

Abstract: The first detailed photoluminescence (PL) study of as-grown CdGeAs 2 samples obtained from three different sources is presented. The study was carried out in the 5-100 K temperature range and laser excitation densities 0.5-5 W cm −2 . PL spectra collected on samples from all sources showed a PL band near 355 meV which is assigned to an (e, A 0 ) transition to the deep native double acceptor 315 meV above the valence band edge. Samples from one source which contained substantially lower levels of oxygen also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
2
14
0
Order By: Relevance
“…CGA with moderate to high optical absorption has generally been found to exhibit two photoluminescence (PL) bands at 0.35 and 0.55 eV, respectively [12][13][14]. The band at 0.35 eV has been assigned to a transition from a shallow donor to a deep acceptor [12,14,15].…”
Section: Impurities and Dopantsmentioning
confidence: 99%
See 1 more Smart Citation
“…CGA with moderate to high optical absorption has generally been found to exhibit two photoluminescence (PL) bands at 0.35 and 0.55 eV, respectively [12][13][14]. The band at 0.35 eV has been assigned to a transition from a shallow donor to a deep acceptor [12,14,15].…”
Section: Impurities and Dopantsmentioning
confidence: 99%
“…The band at 0.35 eV has been assigned to a transition from a shallow donor to a deep acceptor [12,14,15]. The PL band at 0.55 eV, which is not present in highly transparent material, has been suggested to be related to a donorshallow acceptor pair recombination process [12][13][14]. Optical absorption at 5.5 mm, which has varied between 0.4 [11] and 18.4 cm À1 [16], has been attributed, based in part on PL data, to be intraband transitions between the two upper valence bands [17,18].…”
Section: Impurities and Dopantsmentioning
confidence: 99%
“…Photoluminescence studies [7][8][9] of bulk CdGeAs 2 crystals have revealed two dominant PL emission bands. One broad band centered near 0.35-0.38 eV has been assigned as either donor-acceptor-pair (DAP) recombination [8], or an (e, A 0 ) transition involving a deep native double acceptor [9].…”
Section: Introductionmentioning
confidence: 99%
“…One broad band centered near 0.35-0.38 eV has been assigned as either donor-acceptor-pair (DAP) recombination [8], or an (e, A 0 ) transition involving a deep native double acceptor [9]. A second band peaking near 0.55 eV was found to shift to high energy with increasing excitation intensity, and it has been observed to shift by tens of meV when the laser spot was scanned across the sample [8,9], although the origin of the shift was not determined. The 0.55-eV band was suggested to be a DAP transition at low temperatures [7][8][9], converting to conduction band-valence band (e, h) recombination for T > 100 K [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation